Laparoscopic cholecystectomy: Conversion rate and complcation - Malla, BR; Joshi, HN; Rajbhandari, N; Shakya, YR; Karki, B; Gyanwali, D; Shrestha, S; Koju, R (Journal of Society of Surgeons of Nepal, 2016)
Introduction and Objective: Laparoscopic Cholecystectomy is the standard surgical treatment for gallbladder disease. However, conversion to open surgery is not the complication. Different centers have reported different conversion rates and post operative complications. The objective of this study is to identify conversion rate and post operative complication of laparoscopic cholecystectomyMaterials and Methods: This retrospective study included all laparoscopic cholecystectomies attempted in Dhulikhel hospital during the year 2015. Files of all patients were reviewed to find out the demography of the patients and the indication of Laparoscopic cholecystectomy. The rate of conversion to open cholecystectomy, the underlying reasons for conversion and postoperative complications were analyzed.Results: Out of 324 cases attempted laparoscopic cholecystetomies, two cases with the history of previous laparotomy were excluded to rule out the bias in the result. Out of 322 cases 226(70.18%)were female and 96(29.81%) were male . The mean age was 38 years. Over all conversion rate to open cholecystetomy was 1.86% with frozen calot’s triangle as the most common reason for conversion. The over all postoperative complication was 1.24% with no major bile duct injury.Conclusion: Laparoscopic cholecystectomy can safely be done with low conversion rate and complication.